Driven colloidal particles in optical potential energy landscapes - Abbott, J (2018)
The dynamic behaviour of colloidal particles driven across one-dimensional optical potential energy landscapes is studied. Colloids are driven with a piezo-stage, manipulated with optical tweezers and magnetic ﬁelds and imaged using optical microscopy. First, the meta-stable horizontal and vertical states of a colloidal rod in a single optical trap close to a ﬂat wall are explored. A colloidal rod is then driven through a periodic optical potential energy landscape. The equilibrium position of a rod driven below the critical velocity is found to vary substantially from that of a sphere due to the friction coeﬃcient of a rod being highly dependent on its proximity to an optical trap. At higher velocities, a colloidal rod is shown to act similarly to a colloidal sphere, exhibiting dynamic mode locking. Colloidal spheres are then driven across a time-dependent one-dimensional optical potential energy landscape with diﬀerent modes of dynamic mode locking being observed. The mode locked step width is shown to vary with the oscillation frequency and the coupling strength between the particle and the optical landscape. The particle transport across the time-dependent landscape is also studied by measuring the eﬀective diﬀusion coeﬃcient which is highly sensitive to the driving velocity and mode locking. Next, chains of interacting colloidal particles are driven through a time-independent optical potential energy landscape. A mismatch between the length scales of the chain and the landscape gives rise to a freely sliding chain in an Aubry-type transition. In this regime a chain exhibits zero static friction despite being subject to a potential energy landscape. Chain motion is inspected for a driven ﬂexible chain that is seen to exhibit breathing modes. Introducing oscillations in the driving force leads to dynamic depinning, which is aﬀected by both the frequency and amplitude of the oscillations. Finally, the stochastic thermodynamics for particles driven across an optical landscape is considered. The work done by a particle in both a time-independent and a time dependent optical landscape is measured. The optical work in a time-independent landscape is shown to be zero. However, the time-dependent counterpart exhibits a ﬁnite amount of work due to the optical landscape. The magnitude of the observed total work is considered in light of the mechanism of particle motion along with analysis of the contributing optical work and driving work.